Beta-carotene status are co-related with pupillary diameter changes in obese & normal adults in relation to prediction of heart disease - Muhammad Jaffar Khan; Usama; Summaya Hanif; Sadia Fatima (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2019)
Several studies have been conducted by antioxidant properties of the Beta-carotenes in relation to their ability like prevention to coronary diseases. Similarly, 3 out of 4 randomized studies have shown that higher intakes or higher blood concentrations of β-carotenes are associated with the reduced risk of the Predictive Heart Disease (PHD). As vitamin A functions as an epithelial membrane regulator and provides immunity. In spite beta-carotene is the precursor of the vitamin A in the body, which also shows proportional relation to the body vitamin A concentration. However, beta-carotene is mostly addressing through its antioxidant properties. Similarly, a direct relation to the PHD by the pupil response effected by the pro-vitamin A have not been studied.  Result: Co-relation analysis of beta-carotene suggest significant relation to Pupillary Dynamics- Low intensity (r: 0.469, p-value 0.02) in obese adults. While, association of pupillary threshold was found significant with Pupillary Responsiveness- Low & High intensities in both the BMI groups.